Combined Cr and S poisoning of La0.8Sr0.2MnO3-δ (LSM) cathode of solid oxide fuel cells - Wang, Cheng Cheng; Darvish, S.; Chen, K.; Hou, B.; Zhang, Q.; Tan, Z.; Zhong, Y.; Jiang, San Ping (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Combined chromium and sulfur poisoning for La0.8Sr0.2MnO3-δ (LSM)cathodes of solid oxide fuel cells (SOFCs)were investigated with cathodic current of 200 mA cm−2 under 800 °C for 22 h. After polarization in chromium and sulfur at 800 °C for 22 h, polarization and ohmic resistance for LSM electrodes were 5.1 Ω cm2 and 7.62 Ω cm2, which were larger than values of LSM electrodes after chromium deposition only and sulfur deposition only. EDS, XPS and XRD results showed chromium and sulfur deposition occurred especially in bulk of the electrode, forming SrCrO4 and SrSO4. Compared with chromium deposition only, sulfur deposition only, combined chromium and sulfur deposition was not random and the degradation phenomenon of chromium and sulfur poisoning was much more severe. The combined chromium and sulfur deposition of LSM electrodes was induced by interaction among CrO, SO2 and segregated SrO from LSM electrode. Thermodynamic predictions have been carried out utilizing CALPHAD approach, which were found in agreement with observed experimental results.